2017
DOI: 10.1002/em.22148
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage and circulating cell free DNA in greenhouse workers exposed to pesticides

Abstract: Pesticides widely used in agriculture and other applications have been linked to cancer and other diseases through several potential mechanisms. The goals of this study were to assess DNA damage in lymphocytes by the cytokinesis-block micronucleus assay (CBMN), and to measure circulating cell free DNA (ccf-DNA) in the blood of pesticide-exposed greenhouse workers and matched controls living in the same area. CBMN was applied to peripheral blood lymphocyte samples taken at different times (spring and autumn) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…We found a positive correlation between the MN and NBUD formation in the patients. A similar correlation was observed in previous studies (7,8). We could suggest that there might be a common mechanism for the formation of MN and NBUD in the patients with hearing loss.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found a positive correlation between the MN and NBUD formation in the patients. A similar correlation was observed in previous studies (7,8). We could suggest that there might be a common mechanism for the formation of MN and NBUD in the patients with hearing loss.…”
Section: Discussionsupporting
confidence: 91%
“…The CBMN assay was applied to the blood samples to determine the frequency of MN, NPB, and NBUD in both groups ( Figure 2). The method was carried out as described by Fenech (6) and routinely used by our group (7,8). Five ml of the blood sample was taken from each donor in a sterile heparinized tube for all the participants.…”
Section: Cytokinesis-block Micronucleus Cytome (Cbmn) Assaymentioning
confidence: 99%
“…The same circadian rhythmicity, with higher cfDNA levels at mid-day, was observed in colorectal cancer patients of stages I-III, but not stage IV [26]. Environmental exposures, such as exposure to pesticides, may influence the levels of cfDNA; these levels were found to be higher in males than in females [27]. Finally, age is a significant covariable when one studies relative cfDNA amounts at specific genomic locations, such as transcription start and termination sites, or cfDNA-associated methylation signals, corresponding to different tissue types [28] (Fig.…”
Section: Critical In Vivo Pre-analytical Factorsmentioning
confidence: 58%
“…In patient cohorts and workers exposed to occupational hazards, most studies (21/24) report no differences in cirDNA between males and females. A single study of 72 greenhouse workers reported higher cirDNA level in males ( Çayir et al, 2018 ), but the remaining two patient studies reported higher cirDNA in females ( Karlas et al, 2017 ; Kim et al, 2014 ). However, of these, one analysis, conducted in 30 gastric patients, had imbalanced sample numbers with 23 males and only 7 females ( Kim et al, 2014 ), while the other only saw the association with long cirDNA fragments (222 bp), with no effect on short fragments (90 bp) ( Karlas et al, 2017 ).…”
Section: Biological Factorsmentioning
confidence: 98%